Analysis of the range of drugs for the treatment of arterial hypertension presented on the pharmaceutical market of Ukraine - Verkhovod, Viktoria; Kryklyva, Iryna; Karpenko, Liliya (Annals of Mechnikov's Institute, 2022)
Introduction. High blood pressure (BP) is a major risk factor in the population leading to premature mortality. People with high blood pressure need early detection and pharmaceutical care. The aim of our work is to analyze the range of antihypertensive drugs presented on the pharmaceutical market of Ukraine in terms of the pandemic caused by coronavirus infection COVID-19, to justify the choice of the optimal drug. Materials and methods. The analysis of the assortment of antihypertensive drugs presented on the domestic pharmaceutical market was performed following the State Register of Medicinal Products (SRMP) and the Register of Medicinal Products Subject to Reimbursement (RMPSR), as of August 5, 2021. According to the ATC classification, the following groups were analyzed: С02 - hypotensives, С03 - diuretics, С07 - b-adrenoceptor blockers, С08 - calcium antagonists, С09 - agents that affect the renin-angiotensin system. Methods of analytical-comparative, systematic, logical, graphic, mathematical, and statistical analysis were used. Results and discussion. It has been found that according to the SRMP of Ukraine as of January 1, 2022, the group of antihypertensive drugs includes 665 trade names. The drugs are presented in seventeen dosage forms, among which the largest share is occupied by solid dosage forms, such as tablets (55.77%) and film-coated tablets (29.84%). 151 drugs in this group are included in the Affordable Medicines program and are presented in the form of tablets. For further research, enalapril was chosen as the "gold" standard among angiotensin-converting enzyme inhibitors. Conclusions. It has been established that the assortment of antihypertensive drugs presented in the SRMP of Ukraine is much wider than in the RMPSR. There is import dependence of the market segment of antihypertensive drugs. But the share of drugs from domestic manufacturers that have joined the "Affordable Medicines" program is 63%. The improvement of the technology of enalapril maleate tablets, which will be presented in the next publication has been substantiated. Keywords: arterial hypertension, antihypertensive drugs, market analysis, enalapril DOI: 10.5281/zenodo.6350367